2020
DOI: 10.13057/biodiv/d211202
|View full text |Cite
|
Sign up to set email alerts
|

Liver metabolic activities of Pasundan cattle induced by irradiated chitosan

Abstract: Abstract. Mushawwir A, Arifin J, Darwis D, Puspitasari T, Pengerteni DS, Nuryanthi N, Perman R. 2020. Liver metabolic activities of Pasundan cattle induced by irradiated chitosan. Biodiversitas 21: 5571-5578. A total of one hundred and twenty-five, 2-3 year old male Pasundan cattle were used as livestock samples during the three months of this research. They were selected from the local cattle breeding and development center in Ciamis. The animal samples were randomly allocated to 5 treatment groups. One group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
0
20
0
1
Order By: Relevance
“…Furthermore, in association with the research reported [21,22], chitosan supplementation significantly increased the rate of lipolysis, reduced the rate of adipocyte hypertrophy, triglyceride accumulation, and activity of lipoprotein in adipose tissue of the epididymis, also decreased the activity of liver enzymes [24] related to lipid biosynthesis [25]. Chitosan supplementation has been reported to activate phosphorylated adenosine monophosphate (AMP) significantly-activated protein kinase (AMPK) [26,27], and a high-fat diet induces the expression of lipogenic transcription factors (Peroxisome Proliferator-Activated Receptor Gamma/PPAR-γ and sterol receptor element-binding protein 1c/ SREBP1c) [28] in the liver and adipose tissue -29,30].…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, in association with the research reported [21,22], chitosan supplementation significantly increased the rate of lipolysis, reduced the rate of adipocyte hypertrophy, triglyceride accumulation, and activity of lipoprotein in adipose tissue of the epididymis, also decreased the activity of liver enzymes [24] related to lipid biosynthesis [25]. Chitosan supplementation has been reported to activate phosphorylated adenosine monophosphate (AMP) significantly-activated protein kinase (AMPK) [26,27], and a high-fat diet induces the expression of lipogenic transcription factors (Peroxisome Proliferator-Activated Receptor Gamma/PPAR-γ and sterol receptor element-binding protein 1c/ SREBP1c) [28] in the liver and adipose tissue -29,30].…”
Section: Resultsmentioning
confidence: 83%
“…Impaired liver function results from damage to hepatocytes which causes changes in transport function and membrane permeability, leading to the release of SGPT, SGOT, and -GT enzymes in the cytoplasm into blood circulation [24]. This is because the Transaminase Enzyme acts as a catalyst in the process of transferring amino groups from alpha-amino and alpha-keto acids [25,26]. In addition, disturbances in liver function are caused by oxidative stress due to the presence of free radicals in the body, which are reduced by antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, disturbances in liver function are caused by oxidative stress due to the presence of free radicals in the body, which are reduced by antioxidants. Antioxidants can be obtained from outside the body (food) or self-produced [25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…The activity of glycogenolysis and glycolysis is reduced by irradiated chitosan, while the biochemical conditions of liver cells improve (reducing glutamate oxaloacetate transaminase, glutamate pyruvate transaminase, creatinine, creatinine kinase). This is an ideal environment for the metabolism of Pasundan bulls to improve their growth and reproduction (Mushawwir et al 2020). The rate of energy supply via other pathways, such as glycogenolysis, is slowed by IC administration (a decrease in glycogen breakdown in liver cells).…”
Section: Reviewmentioning
confidence: 99%